You can't stay here forever ebook - Lin, Katherine (2023)
Named a must-read book of summer by: Good Morning America, People, the San Francisco Chronicle, the Los Angeles Times, the Boston Globe, and the Philadelphia Inquirer and one of the best books of the year by the New York Post Desperate to obliterate her past, a young widow flees California for the French Riviera in this compelling debut, a tale of loss, rebirth, modern friendship, and romance that blends Sally Rooney's wryness and psychological insight with Emma Straub's gorgeous scene-setting and rich relationships. Just days after her young, handsome husband dies in a car accident, Ellie Huang discovers that he had a mistress—one of her own colleagues at a prestigious San Francisco law firm. Acting on impulse—or is it grief? rage? Probably all three—Ellie cashes in Ian's life insurance policy for an extended stay at the luxurious Hotel du Cap-Eden-Roc in Antibes, France. Accompanying her is her free-spirited best friend, Mable Chou. Ellie hopes that the five-star resort on the French Riviera, with its stunning clientele and floral-scented cocktails, will be a heady escape from the real world. And at first it is. She and Mable meet an intriguing couple, Fauna and Robbie, and as their poolside chats roll into wine-soaked dinners, the four become increasingly intimate. But the sunlit getaway soon turns into a reckoning for Ellie, as long-simmering tensions and uncomfortable truths swirl to the surface. Taking the reader from San Francisco to the gilded luxury of the south of France, You Can't Stay Here Forever is a sharply funny and exciting debut that explores the slippery nature of marriage, the push and pull between friends, and the interplay of race and privilege, seen through the eyes of a young Asian American woman.